Non-invasive measurement method of skin conditions by using Dermalab@ Combo - Ab. Hadi, Hazrina; Mohd Hanif, N; Mohd Sidik, NFA; Mohd Rani, MRN; Mohd Shuhaimi, MS (Penerbit USM, 2014)
Introduction: Skin as a protective barrier from exogenous substances. The aim of the study was to evaluate the realibility of the DermaLab Combo in measuring transepidermal water loss (TEWL) and skin hydration. Methodology 50 male and 50 female students from International Islamic University Malaysia (IIUM) were voluntarily participated in this study. The readings were taken on volar forearm of the volunteers were taken using TEWL probe and hydration pin probe. A set of questionnaire was also distributed to obtain the information about the skin care regime and their daily habits. Results and discussion: Most students who often use moisturizer have lower TEWL value than those who do not use it. A low TEWL is reflects the skin barrier integrity. Skin hydration is also correlated with the use of moisturizers. This is supported by Rosado et al. (2009) who proved that the application of moisturizers can increase stratum corneum hydration. The hydration state of the skin was also higher in volunteers who consumed water of more than 1L per day. It has been reported that fluidity has a positive correlation with stratum corneum hydration. This is because water content at tissue level might redistribute up to the stratum corneum which ultimately hydrated the skin.